Eco-Fatwas and the Challenges for Local ‘Ulamā’ in Addressing Environmental Issues in Indonesia: Evidence from the Riau Province - Ansori, Ansori; Juliansyahzen, Muhammad Iqbal; Prihantoro, Hijrian Angga (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
Despite its abundant natural resources, Riau Province confronts significant challenges, notably forest fires attributed to agricultural practices and land conversion for palm oil cultivation. This article seeks to examine the difficulties encountered by local ‘ulamā’ in addressing environmental issues within Riau Province. The study employs a socio-legal framework to elucidate the responses of local ‘ulamā’ to these challenges, particularly through the application of religious teachings, referred to as eco-fatwas, to comprehend and address the environmental problems prevalent within the region. Utilizing a methodological approach that incorporates in-depth interviews, field observations, and document analysis, the study concludes that the eco-fatwas disseminated by local ‘ulamā’ confront complex challenges, including economic competition, political interests, sectoral egos, and power hegemony. Consequently, this research emphasizes the necessity for the concurrent implementation of cross-community and cross-policy da’wah strategies to effectively mitigate environmental degradation in Riau Province.